Molecular detection and genomic characterization of Samak Micromys paramyxovirus-1 and -2 in Micromys minutus, Republic of Korea - Augustine Natasha; Sarah E. Pye; Seung Hye Cho; Haryo Seno Pangestu; Jieun Park; Kyungmin Park; Sara P. Prayitno; Bohyeon Kim; Jong Sun Lee; Jongwoo Kim; Shailesh Budhathoki; Yeonsu Oh; et al. (Virology Journal)
Abstract Background The discovery of viruses in small mammalian populations, particularly rodents, has expanded the family Paramyxoviridae. The overlap in habitats between rodents and humans increases the risk of zoonotic events, underscoring the importance of active surveillance. Rodent species, such as Apodemus agrarius, are natural hosts for Paramyxoviridae in the Republic of Korea (ROK). However, it is unknown whether Paramyxoviridae is present in Micromys minutus, another common rodent. Method Here, we screened M. minutus collected from the Gangwon Province in the ROK for paramyxoviruses using nested polymerase chain reaction and confirm positive samples by next-generation metagenomic sequencing. Complete paramyxovirus genomes were further characterized by phylogenetic analysis, amino acid similarity, secondary structure, and cophylogeny. Result Overall, 57 of 145 (39.3%) M. minutus kidney samples tested positive for paramyxoviruses. Among them, four whole genome sequences were identified and clustered within the genus Jeilongvirus. One sequence was determined as Samak Micromys paramyxovirus 1 (SMPV-1; 19,911 nucleotides long) and three sequences as Samak Micromys paramyxovirus 2 (SMPV-2; 18,199 nucleotides long). SMPV-1 has a smaller hydrophobic gene and a longer glycoprotein gene than SMPV-2. Cophylogenetic analysis suggests that SMPV-1 evolved through co-divergence, whereas SMPV-2 was inferred to have undergone transfer events. Conclusion These findings highlight the prevalence of paramyxoviruses in the wild and the potential of M. minutus as a natural viral reservoir. The discovery of SMPV-1 and SMPV − 2 also reveals the genetic diversity and evolutionary history of the genus Jeilongvirus in the Paramyxoviridae.